Effects of different operational modes on the flood‐induced turbidity current of a canyon‐shaped reservoir: case study on Liuxihe Reservoir, South China. Issue 26 (15th October 2012) - Wang, Sheng; Qian, Xin; Han, Bo‐Ping; Luo, Lian‐Cong; Ye, Rui; Xiong, Wen
Abstract Suspended matter is an important indicator of water quality in freshwater systems. The flood‐induced turbidity current plays a dominant role in the seasonal dynamic of suspended matter in the Liuxihe Reservoir (23°45′50″N; 113°46′52″E), a large, stratified reservoir at the Tropic of Cancer in southern China. Field measurements show that loading and distribution of suspended matter in the reservoir differ in typical wet, dry and medium years, as a result of different discharge volumes and water level variation patterns. Using historical data and the practical demand for water supply and flood control, we generalized two feasible reservoir operational modes: flood impounding mode (drawing down the reservoir to a low level before flood events to impound inflow during the flooding season) and moderate level change mode (drawing down the reservoir to a moderate level before flood events, then keeping the level within the flood control level during runoff events). To examine the effects of different operational modes and outlet depths on the reservoir's flood‐induced turbidity current, a numerical simulation model was applied in three types of hydrological conditions. The results show that the mode with moderate drawdown and recharge processes can decrease loading of suspended matter in spring and promote turbidity current release during flood events, and upper withdrawal can improve the effects of turbid water release. We suggest that more attention should be focused on water quality management in the reservoir operation stage, severe artificial water level fluctuation being avoided and selective withdrawal becoming an optional management measure. Copyright © 2012 John Wiley & Sons, Ltd.